Analisis Deskriptif Kompetensi Pedagogis Calon Guru: Membangun Pondasi Pendidikan yang Kuat - Susetyawati, MM. Endang; Kintoko, Kintoko (Indo-MathEdu Intellectuals Journal, 2025)
Effective lesson planning can guide the teaching and learning process to become more efficient, provide relevant learning experiences tailored to students' needs, and ensure the achievement of learning objectives. This study aims to analyze the ability of prospective elementary school teachers in designing lesson plans and implementing lessons in elementary schools. This research employs a descriptive qualitative approach, focusing on teacher certification program (PPG) participants who are prospective elementary school teachers. Data were collected through an analysis of lesson planning documents and classroom observation of lesson implementation. The data analyst technique is carried out with three steps of qualitative data analysis in the form of data reduction, data presentation and verification or drawing conclusions. The findings indicate that prospective elementary school teachers are capable of preparing well-structured lesson plans and executing lessons effectively according to their plans. This study suggests that both prospective and active teachers should continuously improve their pedagogical competence to support the success of the teaching and learning process in elementary schools.